Nutritional quality of germinated cowpea flour (Vigna unguiculata) and its application in home prepared powdered weaning foods - Jirapa, P.; Normah, H.; Zamaliah, M.M.; Asmah, R.; Mohamad, K. (Springer, 2001)
Amino acid profiles, protein digestibility, corrected amino acid scores (PDCAAS), chemical scores, essential amino acid indexes, and calculated biological values of control-cowpea flour (CCF), germinated cowpea flour (GCF) prepared from cowpeas germinated at 25 °C for either 24 h or 48 h and weaning foods prepared from cowpea flours were determined. Locally available rice, cowpea flour, banana-pumpkin slurry, and skim milk powder and sucrose in the ratio 35:35:15:15:5 were used to formulate weaning food containing not less than 15% protein. The ingredients were cooked into a slurry and oven-dried to produce flakes. The nutritional and sensory qualities of the weaning products were evaluated. Germination had little effect on the amino acid profile of cowpeas. In vitro protein quality and starch digestibility were improved in germinated cowpea flour. The PDCAAS of 24 h germinated cowpea flour (GCF) weaning food was higher (55.49%) than CCF-weaning food (46.74%). Vitamin A activity in 24 h GCF weaning food was higher than in CCF-weaning food. In vitro starch digestibilities of 24 h GCF and 48 h GCF-weaning foods were higher than that of CCF weaning food. The 24 h GCF-weaning food which had a higher overall acceptability score by sensory panelist than 48 h GCF and CCF-weaning food is recommended for household consumption.